Implementation of Good Corporate Governance Principles in BUMN Companies (Case Study at Perum Jasa Tirta I Region Brantas 3 Mojokerto) - Achmad Ardanu; Rohmawati Kusumaningtias (Jurnal Mutiara Ilmu Akuntansi, 2025)
This study aims to determine the implementation of Good Corporate Governance in BUMN companies (Case study at Perum Jasa Tirta I Region Brantas 3 Mojokerto). The research method used in this study is a qualitative method through a case study approach. Data collection methods used are interviews (Supervisor), observation, questionnaires (30 employees). The results of the study indicate that the Implementation of Good Corporate Governance Principles has been applied by Perum Jasa Tirta I Region Brantas 3 Mojokerto very well. Good Corporate Governance consisting of transparency, accountability, responsibility, independence, and fairness.